Optimization Of Power From Food Waste Using Membrane-Less Microbial Fuel Cell - Anandita, Nadira (Universiti Sains Malaysia, 2020)
Fossil fuels have supported the industrialization and economic growth of countries during the past centuries and it is clear that they cannot indefinitely sustain in a longer time. In this study, Microbial Fuel cell (MFC) had potential solution to generate electricity power and at the same time could reduce the abundant of food waste (1.64 kg/daily, around 8 tonnes/year) which dumped in the landfill. The MFC operated electrochemically incorporate electrogenic bacteria (EB) acted as a biocatalyst in order to produce electricity.